2012
DOI: 10.2119/molmed.2011.00435
|View full text |Cite
|
Sign up to set email alerts
|

Ymer Acts as a Multifunctional Regulator in Nuclear Factor-κB and Fas Signaling Pathways

Abstract: The nuclear factor (NF)-κB family of transcription factors regulates diverse cellular functions, including inflammation, oncogenesis and apoptosis. It was reported that A20 plays a critical role in the termination of NF-κB signaling after activation. Previously, we showed that Ymer interacts and collaborates with A20, followed by degradation of receptor-interacting protein (RIP) and attenuation of NF-κB signaling. Here we show the function of Ymer in regulation of several signaling pathways including NF-κB on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…CCDC50 is a multifunctional regulator of inflammation, cell death, and proliferation. CCDC50 is therefore presumed to be closely related to growth factor signaling or carcinogenesis . In researching the biological consequences of elevated CCDC50S expression in HCC, we provided multiple lines of evidence to demonstrate that CCDC50S accelerates proliferation and promotes migration of HCC cells in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 56%
“…CCDC50 is a multifunctional regulator of inflammation, cell death, and proliferation. CCDC50 is therefore presumed to be closely related to growth factor signaling or carcinogenesis . In researching the biological consequences of elevated CCDC50S expression in HCC, we provided multiple lines of evidence to demonstrate that CCDC50S accelerates proliferation and promotes migration of HCC cells in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 56%
“…Table 14 , and chosen genes are shown in Table 13 , and the functional groups are shown in Table 11 ). Among these upregulated genes are known genes such as epithelium markers keratin 5, 12, and 14, coiled-coil domain containing 50 ( ccdc50 ) that acts as an effector in EGF signaling and negative regulator of NF-kB factor (Tsukiyama et al 2012 ), signaling molecules: wnt3a, wnt7b, growth differentiation factor 3 ( gdf3 ), fibroblast growth factor–binding protein 1 ( fgfbp1 ), proteases cathepsin K and H, extracellular matrix molecules lumican, collagen IX and I, and decorin. A role of these genes in male sex determination and early testis development remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…CCDC50 has been identified as a tyrosine-phosphorylated protein, and the tyrosine phosphorylation of CCDC50 inhibits the downregulation of EGFR [1][2][3] . CCDC50 is also involved in the regulation of RTK-mediated signalling pathways and acts as a multifunctional regulator of the large RTK family and various ligands 2,3,[26][27][28] ; CCDC50 is therefore presumed to be closely related to growth factor signalling. Here, we observed that CCDC50-V2 inhibits the EGFR signalling pathway by downregulating the EGFR level and suppressing the ERK and AKT signalling cascade via EGFR phosphorylation.…”
Section: Discussionmentioning
confidence: 99%